Penelitian Pelayanan Perpustakaan Sekolah di Indonesia Melalui Database Google Scholar: Narrative Literature Review - Sinta Ary Jatmiko; Rully Khairul Anwar; Siti Chaerani Djen Amar; Evi Nursanti Rukmana (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
Introduction. The school library is an information institution located in the school environment which aims as a means for students to access all information, in the school library there must be library services. Library service is very important for the library because the service itself has a big impact on users who want to find information in the library. The purpose of this research is to find out how appropriate school library services are in Indonesia. Data Collection Methods. This research uses a narrative literature review method from references related to school library services in Indonesia, the references analyzed are ten references taken through google scholar with reference criteria from 2013-2023. Data Analysis.The results of the analysis of research methods show that school library services in Indonesia have partially met service standards, Results and Discussion.the types of services used are mostly circulation services and reference services. Some schools have also implemented information technology to assist librarians in cataloging, classifying, and processing other library materials. Many school library services in Indonesia have indeed met the standards, but there are still library services that are still manual in processing library materials. This is based on some librarians who are not library science graduates, besides the age of librarians who do not understand how to use the internet. Conclusion. The conclusion obtained from this research is that school library services in Indonesia have mostly met service standards, but there are still some that have not. The use of information technology has also been done in school libraries in Indonesia.